Village Baseline Study: Site Analysis Report for Yabello – Borana, Ethiopia - Onyango, Leah; Mango, Joash; Desta, S.; Tezera S; Kurui, Zena; Wamubeyi, B.; Mohammed A; Fatuma A (2012)
The village baseline of Denbela Saden village in the CCAFS benchmark site of Yabello in Ethiopia took place from 10th to 12th August 2011. Focus group discussions were conducted separately for men and women. Denbela Saden is a Borana pastoralist village located in a semi-arid area where the dominant vegetation is grass, scrub and acacia trees. It faces inadequate and low quality pasture due to encroachment by bushes, livestock overstocking, and human settlement, all related to a government policy of encouraging permanent settlement of the pastoralists as opposed to the former system of nomadism. The increasing population and the settlement of the community have amplified the need for crop cultivation to complement weakened pastoral production. Cultivation is dependent on often inadequate and unreliable rainfall, and takes place in the valley beds. Crop residues are not incorporated into the soil but used to feed animals. Not surprisingly, yields are very low. Government agricultural extension services do not add much value to cultivators because they focus on livestock services in this area. Two parallel governance systems co-exist in Denbela Saden village, namely the traditional customary system and the modern government system, and the challenge is to create a win–win situation where the operations of these systems are synchronized. The government describes the area as chronically food insecure, and it is not surprising that more than half of the 16 groups/organisations working in the region address food security issues.